Rectal malakoplakia simulating a locally advanced rectal cancer: a case report - Silva, André A.; Pires, Guida C.; Simões, Liliana V.; Lourenço, Beatriz R.; Rocha, Catarina C.; Meireles, Lília J. (International Surgery Journal, 2024)
Malakoplakia is a rare and chronic granulomatous disease, resulting from the accumulation of large granular macrophages containing basophilic inclusion bodies in the cytoplasm named Michaelis-Gutmann bodies. The gastrointestinal tract is the second most common site after the urinary tract, though malakoplakia has the potential to manifest in multiple organs. Rectal malakoplakia is difficult to diagnose due to its unspecific clinical and radiological presentation, usually mimicking a malignancy. Most report cases are associated with immunosuppressive diseases or chronic prolonged illness. We present the case of a 64-year-old male with a history of anal pain. A pelvic magnetic resonance imaging showed a rectal mass with 38 mm invading the mesorectum. Colonoscopy was performed confirming a mass-like lesion and biopsies were taken. Histopathological examination revealed features consistent with malakoplakia. The patient underwent long-term oral antibiotic treatment and during follow-up there was a regression of the lesion and resolution of symptoms.